Diversification of Czech obstetrics - Roztočil, Aleš (Journal of Nursing, Social Studies and Public Health, 2014)
We are members of the EU. The EU legislation has greater legal force than the Czech one. It includes Convention of Biomedicine and Charter of Human Rights and Freedoms. In the area of obstetrics, not all workplaces respect the European legislation. We respect Convention on Biomedicine: not benefit, but the will of the patient is the doctor's supreme command? Do we feel as advisers and helpers of a pregnant woman and an expectant mother, or those educated and clever who know what is the best for her, and she does the best when obeys? Can we reflect psychosocial changes in obstetrics which are common to the west of our borders? The topic of pregnancy concerns maternity hospitals only marginally. The main issue: the woman can choose an outpatient gynaecologist, but a midwife not yet. Change is on the way. Only after discharging herself against medical advice may she refuse the recommended procedure, or vice versa, may she choose this procedure, which is not reimbursable, as an above-standard service (oh the Constitutional Court!). The Czech population of pregnant women has in increasing rate the knowledge about the world trends in obstetrics, and they are not willing to settle for the offered traditional medical management of childbirth. Therefore it is necessary to diversify our obstetrics and to enable every woman to have a labour according her wishes. In the future, our unified obstetrics is no longer sufficient. In most Czech textbooks on obstetrics, the medical management of labour is the only alternative. It is the part of the Recommended Procedure of the Section on Perinatal Medicine of ČGPS (Czech Gynaecological and Obstetrical Society). Most women still adopt an attitude: “Do with me what you want, I wish only it is over.” Many of our obstetricians feel safe in this system and they can hardly imagine any changes. Natural childbirth in maternity hospital has 10 simple rules. The number of women who require this type of delivery is increasing. If any complications arise, the female clients understand that it is necessary to pass to the classical medical procedures. It is the only alternative so far how to discourage women from the risky home birth which is still considered to be dangerous in our conditions. Our obstetrical departments still take a cautious approach to this initiative. Outpatient delivery is not the problem of obstetrics, rather than neonatology. From the economic point of view, it is currently more advantageous in the system of DRG. Birth houses are a common part of the obstetric system in many EU countries. Maintaining the safe conditions, a birth house should not be an obstetric problem even in our country. The women choose a home birth not on the first place, but after the experiences with our standard obstetrics (artificial rupture of membranes, oxytocin, episiotomy, unexplained surgery, Kristeller maneuver, etc.) or because of primary fear of an ordered obstetrics. It is only the matter of time when the women labouring at home are not depended on undeclared work of midwives and Emergency and Rescue Service, and when the state have to guarantee them a professional help. At present days, programmed childbirth is hopefully a trouble-free, marginal part of our obstetrics. Provided the meeting of conditions and induction scheme, it is highly efficient. Caesarean section is not provided on mere unjustified request. The pregnant woman has always some reason – especially psychological – for refusing the vaginal delivery: case history, fear of pain, worries about the fate of a baby when hypoxia suddenly arises, vaginal extraction surgery, alteration of subsequent vita sexualis , late effects, especially disorders of pelvic stability and incontinence. What are the complications of Caesarean section and subsequent pregnancy considering the birthrate of Czech women? This problem has not to be solved any more west of our borders.
Keywords: indukovaný porod; dospělí; Female; Adult; ženské pohlaví; Health Care Reform; porod; lidé; těhotenství; předčasná porodní činnost; Obstetrics; vedení porodu; Natural Childbirth; Parturition; Risk Factors; Delivery, Obstetric; reforma zdravotní péče; rizikové faktory; porodnictví; Cesarean Section; Obstetric Labor, Premature; Pregnancy; Labor, Induced; přirozený porod; císařský řez; Humans